Prioritizing mitigation pathways in land use and food systems: A systematic framework to assess opportunities - Martius, C.; Pingault, N. (CIFOR-ICRAF, 2025)
The global food system generates substantial greenhouse gas (GHG) emissions, amounting to 13–23 GtCO₂e annually, or 23–42% (average: 31%) of the total global net anthropogenic GHG emissions. Yet, despite its importance, the food system is still rarely considered holistically in climate policies, strategies and plans. To help fill this gap, this paper develops a simple but systematic, comprehensive and integrated framework to assess and rank alternative mitigation options in land use and food systems, based on their desirability (what we should do) and feasibility (what we can do). This framework consists of 23 indicators covering the six dimensions of feasibility defined by the Intergovernmental Panel on Climate Change (IPCC), namely: the geophysical, environmental-ecological, technological, economic, sociocultural and institutional dimensions. Such a framework could help policymakers to raise the ambition of their Nationally Determined Contributions (NDCs) and climate policies by identifying and prioritizing ‘low-hanging fruits’, i.e., mitigation options that have the highest transformative potential; can be implemented the most quickly and easily; and are the best adapted to national or local conditions, priorities and needs.